Aesthetic Outcomes and Patient Satisfaction in SMAS Plication Varuses Deep Plane Facelift: A Comparative Study - Kamal Uddin Khan, Farzana Abdullah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Facelift surgery is a cornerstone of facial rejuvenation, with various techniques developed to address aging changes. SMAS (Superficial Musculoaponeurotic System) plication and deep plane facelift represent two of the most commonly employed procedures, each with distinct anatomical targets and outcomes. This study aimed to compare the aesthetic results and patient satisfaction following SMAS plication versus deep plane facelift in a population from Balochistan, Pakistan. Materials and Methods: A prospective, comparative study was conducted at Bolan Medical Complex Hospital, Quetta, from February 2022 to October 2022. Ninety patients (45 in each group) undergoing elective facelift were enrolled. Group A underwent SMAS plication while Group B received deep plane facelift. Inclusion criteria included age 40–65 years, ASA I–II, and no prior facial surgery. Exclusion criteria included coagulopathy, autoimmune disease, or facial trauma. Aesthetic improvement was evaluated by blinded assessors using the Global Aesthetic Improvement Scale (GAIS) at 3 and 6 months post-operatively. Patient satisfaction was measured using Visual Analog Scale (VAS) and FACE-Q questionnaire. Data were analyzed using SPSS v26. One-way ANOVA and Pearson correlation tests were applied to determine statistical significance (p<0.05). Results: Mean age was 53.4 ± 6.2 years in Group A and 52.8 ± 5.9 years in Group B. No significant demographic differences were found. Group B showed significantly higher GAIS scores (mean 4.2 vs. 3.5, p=0.003) and VAS satisfaction (8.6 ± 0.9 vs. 7.8 ± 1.1, p=0.005). FACE-Q scores also favored deep plane technique in areas of mid-face fullness and lower face contour. Complication rates were comparable between groups. A strong positive correlation (r=0.71, p<0.001) was noted between aesthetic scores and patient satisfaction. Conclusion: Deep plane facelift offers superior aesthetic outcomes and higher patient satisfaction than SMAS plication, making it a preferable option for comprehensive facial rejuvenation. However, individualized patient selection and surgical expertise remain critical for optimal outcomes. Keywords: Facelift, SMAS Plication, Deep Plane Facelift, Aesthetic Surgery, Patient Satisfaction, Balochistan, Pakistan.